PhETs Photoelectric Effect Simulation: Experiments and Analysis for Classroom Practice - Pacala, Frank Angelo (Asian Journal of Science Education, 2023)
This paper describes the use of the PhET simulator on the photoelectric effect to explore the behavior of electrons in metal when exposed to light with differing frequencies. Using this simulation, students can be able to observe variations in electron emission when changing various parameters such as intensity or frequency of light. This paper is experimental research to test the PhET simulator on the photoelectric effect in terms of the guiding relationship in the photoelectric effect. This also analyzed the PhET simulation for improvements in classroom activities.The main tool of this research is a computer capable of running the PhET simulation. It was found that all principles of the photoelectric effect are followed by the simulation. This includes if there is an emission of electrons, the relationship between the kinetic energy of the electron and frequency, and the relationship photoelectric current and light intensity. However, it was observed that there is no work function of the metals on the simulation and this can have an effect the prediction if there is an emission or not. The graphs generated of the simulation contains error because of the thick line graph. It would be better for classroom practice if these gaps are bridged and teachers manage to adopt the simulation.